Demand for measles and yellow fever vaccines for children in Ghana: are socio-economic, demographic and Geographic factors relevant? - Immurana, Mustapha; Urma, Arabi (International Journal of Accounting and Economics Studies, 2016)
One of the best ways of Preventing Measles and Yellow fever which are dangerous killers of children is through vaccination. Therefore given the absence of research to the best of our knowledge on the factors that affect demand for Measles and Yellow fever vaccines among children in Ghana, this study investigated the socio-economic, demographic and geographic factors that affect the demand for Measles and Yellow fever vaccines among children in Ghana. By using data from the 2014 Ghana Demographic and Health Survey and the binary probit model, the study among other findings revealed that, Children in the Western region were less likely to have received both the Measles 1 and Yellow fever vaccines. Also urban children and children with unemployed mothers were found to be less likely to have received the Measles 1, Measles 2 and Yellow fever vaccines relative to rural children and children with employed mothers respectively. Also Traditional/Spiritualist/No religion faith children were found to be less likely to have received the Yellow fever vaccine. Further, uneducated mothers, mothers without health insurance and non-wealthy households were found to be less likely to demand the Measles 2 vaccine for their children. This study therefore concludes that Socio-Economic, Demographic and Geographic Factors are relevant determinants of demand for measles and yellow fever vaccines among children in Ghana.
Keywords: Demand for Health; Child Health; Immunisation; Measles Vaccine; Yellow Fever Vaccine; Ghana.